Issues and current Developments in the conservation of indigenous African domestic animal diversity - Rege, J.E.O. (5th World Congress on Genetics Applied to Livestock Production, 1994)
Indigenous domestic animal diversity constitute a major valuable asset for Africa and for the world. In Africa, indigenous livestock breeds, support the majority of smallholder rural farmers for whom these genetic resources are essential for improved nutrition, income and as a secure form of investment. They also provide the only practical means of using vast areas of natural grasslands in regions where crop production is impractical. However, the accelerating demands of a growing human population and pressures of economic Development are affecting the security and survival of these animal genetic resources. There is an increasing tendency to introduce exotic germplasm and/or to concentrate on a narrow range of supposedly more profitable ones. Consequently, native breeds which have been naturally selected for the local environments and are therefore best adapted, are threatened. Unfortunately, most of these breeds are, at best only superficially characterized. Additionally, population statistics on the basis of which the extent of threat could be determined is lacking in most cases. For many breeds, the most rational conservation strategy will be as functioning parts of the production system, i.e. through sustained utiliasation. However, extent of use of a breed depends on awareness of its existence and potential information on its characteristics. This paper summarises the issues and current Developments in characterization, conservation and utilization of indigenous African domestic animal diversity.